MANAJEMEN KELAS DALAM MENCIPTAKAN SUASANA BELAJAR YANG KONDUSIF; UPAYA PENINGKATAN PRESTASI BELAJAR SISWA - Abdul Hamid Wahid; Chusnul Muali; Mutmainnah Mutmainnah (IAIN Batusangkar, 2018)
This paper contributes a lot to the establishment of education in student learning, especially in improving students' active thinking ability. This is due to the lack of qualified sources of educators and hali is focused on educators, because the ability to manage the class become one of the characteristics of a professional teacher. Professional teachers not only have the ability to manage the class well but also skilled in organizing learners to always play an active role and able to improve achievement in learning. The main task of the teacher is to create an atmosphere in the classroom so that the interaction of teaching and learning can motivate the students to learn well and earnestly. For this reason the teacher should have the ability to do good teaching and learning interactions. One capability that is very important is the ability to manage classes. Teachers with all their abilities, students with all backgrounds and individual traits, curriculum with all its components, and materials and learning resources with all its subjects meet and chime and interact in the classroom. In fact, activities that occur in the classroom determine the outcome of an education and learning. Therefore, good classroom management is needed, effective and efficient for teaching and learning activities to run well and educational objectives can be achieved.